Association of functional (GA)n microsatellite polymorphism in the FLI1 gene with susceptibility to human systemic sclerosis. (22nd July 2020) - Yamashita, Keita; Kawasaki, Aya; Matsushita, Takashi; Furukawa, Hiroshi; Kondo, Yuya; Okiyama, Naoko; Nagaoka, Shouhei; Shimada, Kota; Sugii, Shoji; Katayama, Masao; Hirohata, Shunsei; Okamoto, Akira; et al.
Abstract: Objective: Susceptibility genes that can account for characteristic features of SSc such as fibrosis, vasculopathy and autoimmunity remain to be determined. In mice, deficiency of Friend leukaemia integration 1 transcription factor (Fli1) causes SSc-like disease with these features. The human FLI1 gene contains (GA) n microsatellite, which has been shown to be associated with expression level. Because microsatellite polymorphisms are difficult to capture by genome-wide association studies, we directly genotyped FLI1 (GA) n microsatellite and examined its association with SSc. Methods: Genomic DNA from 639 Japanese SSc patients and 851 healthy controls was genotyped for (GA) n microsatellite using the fragment assay. The cut-off repeat number for susceptibility to SSc was determined by receiver operating characteristics (ROC) analysis. Association with susceptibility and clinical characteristics was examined using logistic regression analysis. FLI1 mRNA levels were determined using quantitative RT-PCR. Results: Based on the ROC analysis, (GA) n alleles with ≥22 repeats were collectively defined as L alleles and alleles with ≤21 repeats as S alleles. (GA) n L alleles were significantly associated with susceptibility to SSc ( P = 5.0e-04, odds ratio 1.34, additive model). Significant association was observed both in diffuse cutaneous and limited cutaneous SSc. Among the SSc, (GA) n L alleles were significantly enriched in the patients with a modified Rodnan total skin thickness score ≥10 compared with those with a score <10. FLI1 mRNA levels were significantly decreased in healthy controls carrying (GA) n L alleles as compared with non-carriers. Conclusion: Extended repeat alleles of FLI1 (GA) n microsatellite may be associated with lower FLI1 mRNA levels and susceptibility to human SSc.